Haptoglobin and serum amyloid a in subacute ruminal acidosis in goats (2010)
Ruminal acidosis is a frequent disorder that occurs in goats as a consequence of feeding mistakes in animals not adapted to a diet of easily fermentable carbohydrates. The subacute form of the disease is difficult to diagnose because no apparent signs are shown and the acid-base parameters may remain within the normal range. The present study aimed at testing the hypothesis that haptoglobin (Hp) and serum amyloid A (SAA), the two major acute phase proteins in ruminants, may be useful as markers of subacute acidosis in goats. A subacute acidosis was induced in six Murciano-Granadina goats through a diet of 60% mixed feed-40% alfalfa hay offered during 5 days to goats not adapted to eat mixed feed. Two goats were rumen-fistulated to investigate the effect of feeding on ruminal pH. Sampling of blood and urine of all animals was done before the induction of the acidosis, during 5 days after the onset of induction and for 18 days after the induction (recovery period). Ruminal pH in the fistulated goats dropped to less than 5.5 during the induction period, and half of the goats had diarrhea on the third day after the induction of acidosis. Acid-base parameters showed that the acid-base compensatory mechanisms were efficient in maintaining the equilibrium. Serum Hp had a moderate increase during the induction period, while SAA did not change. These results suggest that Hp might be a potential marker for ruminal acidosis in goats.